Gut microbiota dysbiosis characterized by abnormal elevation of Lactobacillus in patients with immune-mediated necrotizing myopathy - Liang, Xiuping; Li, Yanhong; Cheng, Lu; Wu, Yinlan; Wu, Tong; Wen, Ji; Huang, Deying; Liao, Zehui; Tan, Chunyu; Luo, Yubin; Liu, Yi (Frontiers in Cellular and Infection Microbiology, 2023)
Aim The gut microbiota plays an important role in human health. In this study, we aimed to investigate whether and how gut microbiota communities are altered in patients with immune-mediated necrotizing myopathy (IMNM) and provide new ideas to further explore the pathogenesis of IMNM or screen for its clinical therapeutic targets in the future. Methods The gut microbiota collected from 19 IMNM patients and 23 healthy controls (HCs) were examined by using 16S rRNA gene sequencing. Alpha and beta-diversity analyses were applied to examine the bacterial diversity and community structure. Welch’s t test was performed to identify the significantly abundant taxa of bacteria between the two groups. Spearman correlation analysis was performed to analyze the correlation between gut microbiota and clinical indicators. A receiver operator characteristic (ROC) curve was used to reflect the sensitivity and specificity of microbial biomarker prediction of IMNM disease. P < 0.05 was considered statistically significant. Results Nineteen IMNM patients and 23 HCs were included in the analysis. Among IMNM patients, 94.74% (18/19) of them used glucocorticoids, while 57.89% (11/19) of them used disease-modifying antirheumatic drugs (DMARDs), and the disease was accessed by MITAX (18.26 ± 8.62) and MYOACT (20.68 ± 8.65) scores. Participants in the groups were matched for gender and age. The diversity of the gut microbiota of IMNM patients differed and decreased compared to that of HCs (Chao1, Shannon, and Simpson indexes: p < 0.05). In IMNM patients, the relative abundances of Bacteroides, Roseburia, and Coprococcus were decreased, while that of Lactobacillus and Streptococcus were relatively increased. Furthermore, in IMNM patients, Lactobacillus was positively correlated with the levels of anti-signal recognition particle (SRP) antibodies, anti-Ro52 antibodies, and erythrocyte sedimentation rate (ESR), while Streptococcus was positively correlated with anti-3-hydroxy-3-methylglutaryl-coenzyme A reductase (HMGCR) antibodies and C-reactive protein (CRP). Roseburia was negatively correlated with myoglobin (MYO), cardiac troponin T (cTnT), ESR, CRP, and the occurrence of interstitial lung disease (ILD). Bacteroides was negatively correlated with ESR and CRP, and Coprococcus was negatively correlated with ESR. Finally, the prediction model was built using the top five differential genera, which was verified using a ROC curve (area under the curve (AUC): 87%, 95% confidence interval: 73%–100%). Conclusion We observed a characteristic compositional change in the gut microbiota with an abnormal elevation of Lactobacillus in IMNM patients, which was accompanied by changes in clinical indicators. This suggests that gut microbiota dysbiosis occurs in IMNM patients and is correlated with systemic autoimmune features.